Platelet-rich plasma attenuates the severity of joint capsule fibrosis following post-traumatic joint contracture in rats - Zhang, Yuxin; Wang, Zengguang; Zong, Chenyu; Gu, Xiaoding; Fan, Shuai; Xu, Lili; Cai, Bin; Lu, Shenji (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Post-traumatic joint contracture (PTJC) mainly manifests as excessive inflammation leading to joint capsule fibrosis. Transforming growth factor (TGF)-β1, a key regulator of inflammation and fibrosis, can promote fibroblast activation, proliferation, migration, and differentiation into myofibroblasts. Platelet-rich plasma (PRP) is considered to have strong potential for improving tissue healing and regeneration, the ability to treat joint capsule fibrosis remains largely unknown. Methods: In this study, we aimed to determine the antifibrotic potential of PRP in vivo or in vitro and its possible molecular mechanisms. The TGF-β1-induced primary joint capsule fibroblast model and rat PTJC model were used to observe several fibrotic markers (TGF-β1, α-SMA, COL-Ⅰ, MMP-9) and signaling transduction pathway (Smad2/3) using histological staining, qRT-PCR and western blot. Results: Fibroblasts transformed to myofibroblasts after TGF-β1 stimulation with an increase of TGF-β1, α-SMA, COL-Ⅰ, MMP-9 and the activation of Smad2/3 in vitro. However, TGF-β1-induced upregulation or activation of these fibrotic markers or signaling could be effectively suppressed by the introduction of PRP. Fibrotic markers’ similar changes were observed in the rat PTJC model and PRP effectively reduced inflammatory cell infiltration and collagen fiber deposition in the posterior joint capsule. Interestingly, HE staining showed that articular cartilage was degraded after rat PTJC, and PRP injection also have the potential to protect articular cartilage. Conclusion: PRP can attenuate pathological changes of joint capsule fibrosis during PTJC, which may be implemented by inhibiting TGF-β1/Smad2/3 signaling and downstream fibrotic marker expression in joint capsule fibroblasts.